Is in vivo Amyloid Distribution Asymmetric in Primary Progressive Aphasia? - Martersteck, Adam (Ann Neurol, 2016)
We aimed to determine whether (18)F-florbetapir amyloid PET imaging shows a clinically concordant, left hemisphere dominant, pattern of deposition in primary progressive aphasia (PPA). Elevated cortical amyloid (Aβ+) was found in 19/32 PPA patients. Hemispheric laterality of amyloid burden was compared between Aβ+ PPA and an Aβ+ amnestic dementia group (n=22). The parietal region showed significantly greater left lateralized amyloid uptake in the PPA group than the amnestic group (p < 0.007), consistent with the left lateralized pattern of neurodegeneration in PPA. These results suggest the cortical distribution of amyloid may have a greater clinical concordance than previously reported.